Upaya Kepala Sekolah dalam Memberikan Supervisi dan Apresiasi Terhadap Kinerja Guru di SDN 2 Sendangmulyo - Tumeko, Dwi Satrio Bagus; Rasiman, Rasiman; Supandi, Supandi (Cetta: Jurnal Ilmu Pendidikan, 2025)
Optimal teacher performance is a crucial component in improving the quality of education, particularly at the elementary level. In this context, the principal holds a strategic role in supporting and encouraging teacher performance through effective supervision and appropriate appreciation. This study aims to describe the principal’s efforts in supervising and giving appreciation to teacher performance at SDN 2 Sendangmulyo. This research uses a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and documentation, with the research subjects consisting of the principal and several teachers as informants. The results show that the principal actively conducts academic supervision through direct classroom monitoring, planned coaching, and systematic evaluation of the teaching and learning process. Supervision is not only intended for assessment but also to guide and improve teaching quality. In addition, the principal provides various forms of appreciation, both moral—such as public praise and recognition in formal forums—and material, such as certificates and incentives. These forms of appreciation have been proven to increase teacher motivation and enthusiasm. Consistent supervision and appreciation efforts have created a more harmonious and productive work environment, improved teacher professionalism, and positively impacted student learning outcomes. In conclusion, constructive supervision and motivational appreciation by the principal are effective strategies to enhance teacher performance in the elementary school setting.